Reframing Parental Involvement as Social Engagement: A Study of Recently Arrived Arabic-Speaking Refugee Parents’ Understandings of Involvement in Their Children’s Education - Cranston, Jerome; Labman, Shauna; Crook, Stephanie (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
The involvement of refugee parents in their children’s education is crucial for academic success and social integration. However, school personnel often seem to struggle to find approaches that will increase recently arrived refugee parents’ involvement with the school. While refugee parents are not a homogenous group, many face uniquely similar and intersecting challenges. Using a qualitative research approach, specifically semi-structured interviews, this study examines the perceptions of one group of Arabic-speaking, recently arrived refugee parents’ perceptions of being and becoming involved in their children’s education after their arrival in Canada. The findings suggest the following factors act as barriers to their involvement: (1) limited language proficiency, (2) competing basic needs, (3) lack of homework, (4) teachers’ limited cross-cultural and interreligious understanding, and (5) sexual health education being a contested shared space. While the findings illuminate what some recently arrived refugee parents regard as barriers, the discussion challenges educational leaders and policy makers to critically question the dominant, normative model of parental involvement that is employed and recommends they reframe their conceptions of parental involvement as social engagement with a school community. Such a reframing may better support recently arrived refugee parents’ integration into their new home country.